SOSIALISASI PENCEGAHAN KEKERASAN SEKSUAL TERHADAP SANTRI DI DAYAH MODERN DARUL ULUM BANDA ACEH - Nurarafah Nurarafah; Jarnawi; Arnita; Husni (STAI Nusantara Kota Banda Aceh, 2026)
Sexual violence against children and adolescents is a serious problem that can occur in various environments, including religious-based educational institutions. Santri, as a vulnerable age group, need adequate understanding of the forms, impacts, and prevention efforts of sexual violence. This community service activity aims to increase the knowledge and awareness of students at Dayah Modern Darul Ulum Banda Aceh regarding the prevention of sexual violence through socialisation and education activities. The methods used include counseling, interactive discussions, and question and answer sessions with students. The results of the activity showed an increase in the santri's understanding of the types of sexual violence, how to protect themselves, and the importance of reporting to trusted parties. This activity is expected to be a preventive measure in creating a safe, comfortable, and fair dayah environment for all santri